Political dominance of the Garin Family in the first district of Iloilo. - Guevara, Dennis Angelo J.
This is a descriptive study of the Political Dominance of the Garin Family in the First District of Iloilo. This study explains why the Garin family became dominant in the first district and describes as the factors for the persistence of their political dominance. It also analyzes the economic contributions of the Garin family in the first district., The study was conducted in the first district using interview guides with open-ended questions for the key informants, who are members of the Garin family, their political allies, and opponents. Interviews were taped. The major findings of this research project is that the Garin family is a new political family. Though some members of the Garins proved themeselves in politics, it was Oscar Garin, the family's patriarch, who transformed the family into a political family. Through time, the Garin has mastered politics in the first district and has established its own political organizations, machinery, and strategies to remain as the dominant political family in their district.